(3TQM dGejI GdYLes - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s; (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s ((3bQjI GdSdGeI (B_ (3GdWGFa s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM UOQ ef JCOH hHYO aEf GdbUjOI GdehSheI HdGejI GdYLe ai WdYI GdTed eG jZfjc Yf RMd hbO TQMgG s
(3BNQgG (B:s
(3hEPG NGeQ Gdghi bdH UH aYdjg dcd Yjf Odjd hGYQa GdCeQ bHd ehbYg aeGdg HYOg acQg fOe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3GdfSNI HgG MhGTs
(3hQO ai cTa GdXfhf L(B2 (3U` (B1537 (3Cf GdZjK GdPi EfSLe ai TQM dGejI GdYLe gi deDdagG UdGM GdOjf Ndjd Hf CjHc GdUaOi GdeJhai SfI (B764 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
Keywords: (3GdeLGejYs